Hybrid electric power train engineering and technology modeling, control, and simulation - Szumanowski, Antoni (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book provides readers with an academic investigation into HEV power train design using mathematical modeling and simulation of various hybrid electric motors and control systems"--Provided by publisher.
Keywords: Hybrid electric vehicles -- Power trains.; elektronické knihy; electronic books